TIPS DAN TRIK BEBAS PLAGIASI DALAM MENYUSUN TUGAS AKHIR (PELATIHAN DAN PENDAMPINGAN PENINGKATAN KEMAMPUAN MAHASISWA DALAM MENGHINDARI PLAGIARISME) - Syafruddin Syafruddin; Suharli Suharli; Adnan Adnan; Riadi Suhendra; Rini Qurratul Aini; Ana Merdekawaty (FKIP Universitas Samawa, 2021)
Plagiarism among students cannot be avoided as science and technology develops recently. Plagiarism is not only done by final year students, it is also carried out by lower-level students in making student assignments. This happens because of easy internet access to find information/data and also the lack of student knowledge regarding plagiarism. The purpose of this activity is that students have knowledge in avoiding plagiarism and have the ability to compose sentences taken from references and compose with their own sentences (Paraphrase). This activity was carried out at the Samawa University FKIP which was organized by the FKIP DPM. The implementation method used consists of three stages, namely the preparation, implementation, and evaluation stages. Activities in the form of lectures and training. Students are very enthusiastic and enthusiastic in participating in this activity, as can be seen from the number of students who ask questions related to the theme presented.